Los cabilderos, Washington y la Constitución de 1917 - Collado, María del Carmen (Anuario de Historia de América Latina, 2017)
This article analyzes the arguments used by American lobbyists to pressure Washington to oppose against the Mexican Constitution of 1917 or articles that affected the interests of miners, oil companies, landowners and merchants in Mexico between 1916 and 1921. These attempts did not prevail, since both the State Department and the White House put national interests ahead of the private interests of investors south of the border during World War I. However, the lobbyists demands did have an impact on foreign policy when America’s position was modified at the end of the war. Ultimately the US government did not adopt the interventionism proposed by the hardliners, who insisted on repealing the Constitution or modifying some of its articles, but instead used diplomatic pressure to defend the interests of its fellow citizens in Mexico.